Evolution of Energy Efficiency of Buildings Using the Guidelines of the European Green Deal Plan - Szymczak-Graczyk, Anna; Kalka, Julia; Ksit, Barbara (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In contemporary literature, there are not many analyses taking into account changing heat transfer coefficients over the years and examining and comparing the variability of insulation thickness in different thermal standards. The article presents the evolution of energy demand taking into account the requirements of the Green Deal. The analysis was carried out using two materials, showing how their thickness changed in relation to the evolving energy requirements.
Keywords: energy efficiency; green deal; building insulation; heat transfer coefficient; thermal standards; energy performance